In Vivo Spinal Distribution of Cy5.5 Fluorescent Dye after Injection via the Lateral Ventricle and Cisterna Magna in Rat Model - Lee, Kee-Hang (J Korean Neurosurg Soc, 2018)
OBJECTIVE: The purpose of this study was to find an optimal delivery route for clinical trials of intrathecal cell therapy for spinal cord injury in preclinical stage. METHODS: We compared in vivo distribution of Cy5.5 fluorescent dye in the spinal cord region at various time points utilizing in vivo optical imaging techniques, which was injected into the lateral ventricle (LV) or cisterna magna (CM) of rats. RESULTS: Although CM locates nearer to the spinal cord than the LV, significantly higher signal of Cy5.5 was detected in the thoracic and lumbar spinal cord region at all time points tested when Cy5.5 was injected into the LV. In the LV injection Cy5.5 signal in the thoracic and lumbar spinal cord was observed within 12 hours after injection, which was maintained until 72 hours after injection. In contrast, Cy5.5 signal was concentrated at the injection site in the CM injection at all time points. CONCLUSION: These data suggested that the LV might be suitable for preclinical injection route of therapeutics targeting the spinal cord to test their treatment efficacy and biosafety for spinal cord diseases in small animal models.